(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Earthquake engineers have taken many precautions in their building designs to protect and minimize destructive effects. In this way, many new design and reinforcement methods have been developed against seismic loads. The use of a pendulum tuned mass damper (PTMD) is one of the developed methods. One of the most important negative aspects of the use of PTMD is the increase in the structural period. Therefore, in this study, the effects of PTMD on periods and mode shapes in symmetrically reinforced concrete water tank model were investigated. For this, two models with and without PTMD were created by the finite element method and modal parameters were compared. As a result of the data obtained, it has been observed that the water tank model makes more balanced displacements, as can be understood from the mode shapes, without increasing the period of the water tank to a dangerous level. It is known that PTMD reduces the seismic effect by acting in the opposite direction to the seismic effect on the structure. Pendulum tuned mass damper can be used in reinforced concrete water tanks, provided that it does not increase period too much.